SINERGITAS BAWASLU DENGAN MAHASISWA DALAM MEMBERIKAN PEMAHAMAN POLITIK DI KELURAHAN SERENGAN: SINERGITAS BAWASLU DENGAN MAHASISWA DALAM MEMBERIKAN PEMAHAMAN POLITIK DI KELURAHAN SERENGAN - Muhammad Kurniawan Budi Wibowo; Aditya Fajri Kurnia Pradana; Umi Musalimah; Luthfia Miftakhul Husna; Rahma Diyas Putri Hamidah; Kurnia Hidayat (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This study examines the synergy of the election supervisory agency (Bawaslu) with students in providing political understanding in Serengan Village. Methods of community service activities (PKM) There are 3 main stages: (1) planning, including Focus Group Discussion (FGD) socialization of clean political activities, preparation of clean political campaign tools and equipment, (2) Implementation, including seminars with the theme of building democracy and maintaining nationality, installation of clean political MMT, (3) Monitoring and evaluation of programs, including Monitoring and evaluation of the success of Seminar programs and the implementation of election monitoring. Partners in the activity are 15 heads of RW and 18 active institutions in Serengan Village. The results showed that the synergy between Bawaslu and students can strengthen efforts to provide political understanding to the community. Through this collaboration, students can act as agents of change that help spread information about the importance of political participation and understanding rights and obligations in the democratic process. Bawaslu provides technical support and access to students to organize counselling events and political campaigns at the kelurahan level. With this synergy, a conducive environment is created to increase the political awareness of the community in Serengan Village. This research provides an important contribution to understanding the active role of students and election supervisory institutions in building a more participatory and Democratic political culture at the local level.